Student’s Response Toward Learning English Vocabulary Using Quizizz Application a Study at Ma Nw Kabar - Muslimaini Muti’ain; Laila Wati; Hamzhani Wathoni; M. Adib Nazri (CV. ULIL ALBAB CORP, 2024)
This study aims at examining the students' response to the use of Quizizz application as a tool to develop their English vocabulary. Qualitative methods was used in collecting data through observation, questionnaires, and interviews. The sample was 15 students of MA NW Kabar who were random selected from 23 students. The findings of the study showed a positive response from students to Quizizz, with three themes emerging. First, students appreciated the interesting features offered by Quizizz in vocabulary learning. Second, it is interactive and helpful in improving their comprehension skills. Third, Quizizz successfully provides motivation and encouragement to students to expand their English vocabulary. Overall, this study suggests that Quizizz has a positive impact on its users by increasing motivation and interest in learning English through its interactive and versatile platform.